Virtual flux vector reconstruction of a PWM rectifier - CHEN Tie-zhu; ZHANG Yong-jun; XIAO Xiong; LUO Ling-bo (工程科学学报)
The virtual flux space vector of a pulse width modulation (PWM) rectifier usually can be calculated by integrating the grid voltage vector. In practice, the pure integral part is replaced with a first-order low-pass filter (FOLP) to counteract the DC offset error and high frequency harmonic interference. However, the FOLP will result in the amplitude variation and phase shift of the grid voltage vector, which can lead to inaccurate observations of the virtual flux. In order to eliminate the effect of the FOLP on the grid voltage, this paper proposes an improved virtual flux orientation strategy based on the vector reconstruction principle. According to the amplitude-frequency characteristics and phase-frequency characteristics of the FLOP, the amplitude and phase of the voltage vector were separately reconstructed to improve the accuracy of the amplitude and phase values in virtual flux estimation. Furthermore, the proposed method was applied to a virtual flux oriented PWM rectifier direct power control system. Simulations and experimental results show that, compared with the traditional first-order low-pass filter, this method improves the accuracy of virtual flux estimation, effectively reduces the DC bus vohage fluctuation in dynamic response, and is more conducive to filter out grid current harmonics control.